Let's first simplify the given equation:
\( 3 - 15x + 24 + 16x = 4x - 24 - 4x \)
Combining like terms on both sides:
On the left side:
- Combine the constants: \(3 + 24 = 27\)
- Combine the x terms: \(-15x + 16x = 1x\) (or just \(x\))
So the left side simplifies to: \(x + 27\)
On the right side:
- Combine the terms with x: \(4x - 4x = 0\)
- The right side simplifies to: \(-24\)
Thus the equation now looks like: \(x + 27 = -24\)
Now we can determine the next best step to solve for \(x\).
To isolate \(x\), you would need to subtract \(27\) from both sides of the equation.
So, the correct response is: Subtract 27 from both sides of the equation.